2009
DOI: 10.1093/jb/mvp149
|View full text |Cite
|
Sign up to set email alerts
|

Role of Nrf2 and p62/ZIP in the neurite outgrowth by carnosic acid in PC12h cells

Abstract: Neurotrophins such as NGF promote neuronal survival and differentiation via the cell surface TrkA neurotrophin receptor. Compounds with neurotrophic actions that are low in molecular weight and can permeate the blood-brain barrier are promising therapeutic agents against neurodegenerative diseases such as Alzheimer's disease. Carnosic acid (CA), an electrophilic compound in rosemary, activates antioxidant responsive element (ARE)-mediated transcription via activation of Nrf2. In the present study, we discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(71 citation statements)
references
References 36 publications
6
65
0
Order By: Relevance
“…Keap1 is a repressor of Nrf2 and functions as an adaptor in the ubiquitination of Nrf2 in Cul3-dependent systems. The Keap1-Nrf2 pathway is regulated by conformational changes in Keap1-Nrf2 interaction in response to oxidative stress [9][10][11]. Consistent with this notion, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 we found that fenofibrate activates the transcription of Nrf2 target genes associated with the down-regulation of Keap1.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Keap1 is a repressor of Nrf2 and functions as an adaptor in the ubiquitination of Nrf2 in Cul3-dependent systems. The Keap1-Nrf2 pathway is regulated by conformational changes in Keap1-Nrf2 interaction in response to oxidative stress [9][10][11]. Consistent with this notion, M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 10 we found that fenofibrate activates the transcription of Nrf2 target genes associated with the down-regulation of Keap1.…”
Section: Discussionsupporting
confidence: 77%
“…Keap1 acts as a substrate for the ubiquitination of Nrf2, dependent of the Cul3-dependent E3 ubiquitination system. Therefore, Keap1 targets Nrf2 for proteasomal degradation under normal conditions [10,11]. Upon oxidative stress, certain cysteine residues of Keap1 are modified; this induces a conformational change in Keap1 and inhibits proteasomal degradation of Nrf2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of the p62 gene is induced by NRF2 upon exposure to electrophiles, reactive oxygen species, and nitric oxide (38,43,49). Furthermore, p62 protein has been reported to stimulate expression of genes containing an ARE in their promoter regions (39).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, dietary supplementation with antioxidants could conceivably protect against the molecular effects of lipid peroxidation, free radicals and ROS and delay the progress of many chronic diseases. Results of the relevant studies showed that there are biologically active compounds in rosemary essential oil exhibiting neuroprotective, antioxidant, anti-carcinogenic and cognition-enhancing properties (Kosaka et al 2010;Zhang et al 2010). It is suggested that the neuroprotective effect of RE occurs partly because of decreased oxidative damage.…”
Section: Introductionmentioning
confidence: 99%